Tadeusz Stryjakiewicz, Alexander Tölle, Robert Kudłak, Paweł Motek, Agnieszka Różalska-Kusza, Magda Wdowicka Profile miejskie – Poznań/ Städteprofile – Posen - Czasopisma, Redakcja (Rozwój Regionalny i Polityka Regionalna, 2010)
Tadeusz Stryjakiewicz, Alexander Tölle, Robert Kudłak, Paweł Motek, Agnieszka Różalska-Kusza, Magda Wdowicka Profile miejskie – Poznań/ Städteprofile – Posen. Bogucki Wydawnictwo Naukowe, Poznań 2009 ISBN 978-83-61320-74-6